2009
DOI: 10.1021/jo900642f
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of anti-Aldol Segments via a Nonaldol Route: Synthetic Applications to Statines and (−)-Tetrahydrolipstatin

Abstract: An asymmetric synthesis of anti-aldol segments via a nonaldol route is described. The strategy involves a highly diastereoselective synthesis of functionalized tetrahydrofuran derivatives from optically active 4-phenylbutyrolactone. Treatment of the tetrahydrofuran derivatives with a Lewis acid and acetic anhydride provided the corresponding ring-opened styrene derivatives. Oxidative cleavage of the styrene derivatives provided access to the anti-aldol segments. The utility of this methodology was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…Of significance is the isolation of the cis a,g-disubstituted g-butyrolactone (52 %i solated yield) as the major product because the cis isomer cannot be prepared by traditional enolate alkylation with an alkyl halide. [16] Forinstance,the alkylation of 11 e with benzyl bromide and LDAa tÀ 78 8 8Cf ormed the thermodynamically more stable trans isomer exclusively.…”
Section: Methodsmentioning
confidence: 99%
“…Of significance is the isolation of the cis a,g-disubstituted g-butyrolactone (52 %i solated yield) as the major product because the cis isomer cannot be prepared by traditional enolate alkylation with an alkyl halide. [16] Forinstance,the alkylation of 11 e with benzyl bromide and LDAa tÀ 78 8 8Cf ormed the thermodynamically more stable trans isomer exclusively.…”
Section: Methodsmentioning
confidence: 99%
“…In the synthesis of the hypocholesterolemic agent 1233A, 34 cycloadduct 96, obtained in 58% yield and as a single stereoisomer, was submitted in reduction, protection, and Heck reactions before hydrolysis of the chiral auxiliary (Scheme 22). 35 Similarly, in the synthesis of the hemisynthetic pancreatic lipase inhibitor tetrahydrolipstatin, 36 carbon chain homologation of cycloadduct 100 through diisobutylaluminum hydride reduction, oxidation, and Wittig reaction occurred without any side reactions. 37 In both cases, the mild conditions for reduction of the chiral auxiliary allowed the preparation of highly functionalized oxygenated compounds.…”
Section: Scheme 20mentioning
confidence: 99%
“…Ghosh et al [26] synthesized ( + )-cryptophycin 52, a potent antimitotic antitumor agent, by using chiral 4-phenyl-γ -butyrolactone as a building block. This γ -lactone was also used for the preparation of other biologically active compounds [27,28] . In addition, Kotkar et al [29] reported the synthesis of ( + )-harzialactone starting with chiral 5-phenyl-γ -pentalactone.…”
Section: Introductionmentioning
confidence: 99%